How arts engagement supported social connectedness during the first year of the COVID-19 pandemic in the United Kingdom: findings from the HEartS Survey. (June 2022) - Perkins, R.; Kaye, S.L.; Zammit, B.B.; Mason-Bertrand, A.; Spiro, N.; Williamon, A.
Abstract: Objectives: This study investigated how adults in the United Kingdom perceived their arts and cultural engagement to facilitate social connectedness over two phases in the first year of the COVID-19 pandemic. Study design: The study used the HEartS Survey, a newly designed online survey tool to capture arts engagement in the United Kingdom and its associations with social and mental well-being, over two phases in 2020: March to May (Phase 1) and October (Phase 2). Methods: Qualitative data were provided at both phases by 581 respondents, who identified which arts and cultural activity they felt most connected them to others and how during the last month. Results: Thematic analysis revealed that, at both phases, arts and cultural engagement was perceived to facilitate social connectedness through four pathways that were also identified prepandemic: social opportunities, sharing, feelings of commonality and belonging and collective understanding. The subthemes shed light on specific ways that respondents used the arts during the pandemic to connect with others, including using the arts: as a catalyst for conversations, to maintain, reinstate or strengthen relationships during social distancing and to facilitate social interactions (Theme 1); to bring people together through shared experiences and sharing of art (Theme 2); to elicit feelings of direct and indirect proximity to others, to connect people with common interests, to feel a sense of belonging to something and to feel part of a collective 'COVID-19 experience' or to feel collectively distracted from the pandemic (Theme 3); and to learn from and about other people and to relate to others (Theme 4). The activity most frequently cited as connecting was watching a film or drama, followed by listening to recorded music. Conclusions: Engagement in arts and cultural activities supported feelings of social connection among adults in the United Kingdom over two phases in the first year of the COVID-19 pandemic, highlighting the importance of access to the arts and culture to support social connectedness.